A Hybrid Analytical-Numerical Model of Heat Generation and Distribution in Friction Stir Welded AA2024 Butt Joints - Seleman, Mohamed M. El-Sayed; Elnaml, Ahmed M.; Ataya, Sabbah; Ahmed, Mohamed M. Z.; Elnekhaily, Sarah A.; Hafez, Khalid M. (International Journal of Integrated Engineering, 2024)
Being a solid-state process, friction stir welding (FSW) is considered a candidate technique for welding critically-microstructure-sensitive materials such as heat-treatable aluminum alloys. A hybrid computational model that employs both analytical and numerical approaches was used to estimate the amount of heat generated in the FSW of AA2024-T4 butt-welded sheets and how it is distributed as a function of time using a 3D transient heat transfer finite element analysis (FEA). Experimental procedures were used to validate the heat distribution in the welded butt joints using candidate rotational and travel speeds from the numerical model. The model outcomes show that rotational speed less than 600 rpm gives insufficient heat input when the optimum travel speed is 25 mm/min while higher rpm would cause overheating and flash formation. Structural and mechanical joint characterizations were performed to ensure the validity of the optimized process parameters. The model recommended parameters give the defect-free butt joints with the best efficiency in terms of ultimate strength. The Vickers hardness profile (W-shaped) for the welds’ cross-sections shows that 600 rpm gives the highest values in all different weld zones compared to that welded at 400 and 800 rpm.